2015
DOI: 10.2147/jir.s84993
|View full text |Cite
|
Sign up to set email alerts
|

Effects of exendin-4, a glucagon like peptide-1 receptor agonist, on neutrophil count and inflammatory cytokines in a rat model of endotoxemia

Abstract: BackgroundSepsis remains a major cause of morbidity and mortality. A variety of strategies targeting modulation of the pro-inflammatory response associated with early sepsis have been reported without clinical success. GLP-1 enhances glucose-stimulated insulin secretion. In addition, it was shown to have anti-inflammatory effects. We hypothesized that treatment with exendin-4, a GLP-1 receptor agonist, would attenuate inflammation and improve glucose control in a lipopolysaccharide (LPS) rat model of inflammat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

4
20
0
2

Year Published

2017
2017
2023
2023

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 33 publications
(26 citation statements)
references
References 31 publications
4
20
0
2
Order By: Relevance
“…Shin et al (29) consistently observed systemic infl ammatory responses such as higher concentrations of proinfl ammatory cytokines TNF-α and IL-6 with LPS, in comparison to control rats. Yanay et al found signifi cantly higher levels of TNF-α, IL-6 and IL-1β in the LPS group than the sham group (30). Our study obtained similar results.…”
Section: Discussionsupporting
confidence: 88%
“…Shin et al (29) consistently observed systemic infl ammatory responses such as higher concentrations of proinfl ammatory cytokines TNF-α and IL-6 with LPS, in comparison to control rats. Yanay et al found signifi cantly higher levels of TNF-α, IL-6 and IL-1β in the LPS group than the sham group (30). Our study obtained similar results.…”
Section: Discussionsupporting
confidence: 88%
“…Incretin-based therapies have revolutionized the care of patients with diabetes mellitus, 4,29,30 and preclinical studies demonstrate anti-inflammatory effects of incretins and suggest benefits in septic animal models. 16,[31][32][33][34] Early clinical trials of exogenous incretin administration to critically ill patients have demonstrated beneficial effects on glycemic control, 35,36 and in this trial we extend those observations to test whether endogenous incretin stimulation can be targeted through provision of enteral dextrose. We hypothesize that increasing circulating incretins using enteral dextrose will decrease systemic inflammation.…”
Section: Discussionmentioning
confidence: 87%
“…The SEEDS trial is novel in its focus on endogenous stimulation of incretin hormones in sepsis. Incretin‐based therapies have revolutionized the care of patients with diabetes mellitus, and preclinical studies demonstrate anti‐inflammatory effects of incretins and suggest benefits in septic animal models . Early clinical trials of exogenous incretin administration to critically ill patients have demonstrated beneficial effects on glycemic control, and in this trial we extend those observations to test whether endogenous incretin stimulation can be targeted through provision of enteral dextrose.…”
Section: Discussionmentioning
confidence: 89%
“…Emerging evidence indicates that inflammation caused by LPS could affect the status of maternal nutrition and placental nutrient transfer. LPS itself has been shown to induce hypoglycemia (Tweedell et al., 2011; Yanay, Bailey, Kernan, Zimmerman, & Osborne, 2015). Wu et al (2018) reported that after intrauterine injection of LPS, magnetic resonance imaging (MRI) showed significantly decreased placental perfusion, and the placental capability in response to maternal glucose challenge was impaired.…”
Section: Discussionmentioning
confidence: 99%